Sosialisasi Penanggulangan Penyakit Hipertensi dan Diabetes Melitus menggunakan Minuman Herbal dari Kayu Manis - Maulita Saraswati; Muhammad Muzammil; Mita Rahma Sekar Ayu; Khoirotun Nisa; Aruma Dini Asiandaru; Hanikatur Rosyidah; Septi Rahmawati; Mustika Arum Mulyaningtyar; Risky Eka Saputra; Salza Mandasari (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension and diabetes mellitus can affect both young and elderly populations. Consuming herbal beverages is one method of managing these conditions, given their minimal side effects. This initiative aims to reduce the prevalence of hypertension and diabetes mellitus by promoting the use of such herbal drinks. The program was implemented through an outreach and presentation strategy divided into three stages: the first stage was preparation, involving data collection, surveys, proposal drafting, and obtaining necessary permits. The subsequent stage was implementation, which included free blood pressure and blood sugar screenings, counseling, and the preparation of herbal beverages. Additionally, this stage involved raising awareness about hypertension and diabetes mellitus—covering definitions, associated risks, and detection methods—as well as introducing non-pharmacological therapy using cinnamon-based herbal drinks. The final stage was evaluation. The results demonstrated an enthusiastic response and a high level of understanding among all participants, evidenced by the active QA session at the end of the activity. Consequently, the community gained knowledge regarding natural ways to treat and manage these diseases using plants readily available in their local environment.